PENINGKATAN EFEK ANTIHIPERTENSI KAPTOPRIL OLEH EKSTRAK ETANOL DAUN BELIMBING WULUH (Averrhoa bilimbi L.) PADA TIKUS HIPERTENSI YANG DIINDUKSI MONOSODIUM GLUTAMAT - Devi Nisa Hidayati; Yance Anas; Siti Nurikha (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2015)
ABSTRACT Hypertension is one of the degenerative disease of health problem  in among people. Bilimbi leaves (Averrhoa bilimbi L.) is one of plants which is have antihypertension effect and contains phytol, dietil phtalat, flavonoid.  This research is aimed  to know influence of ethanol extract of bilimbi leaves (EEBL)   through its on the increase of the antihypertensive effect of captopril in hypertensive rats. This research used a pre-test and post-test matched control group design.   Sample were 30 male Wistar rats  treated with MSG 100 mg/kgBW/day (po) for 14 days to induce hypertension. Hypertensive rats were divided into six treatment groups are  hypertension control group (0.5% CMC-Na 12.5 mL/kgBW/day) and positive control group (captopril 2.5 mg/kgBW/day), and treatment hypertensive rats EEBL (60 and 120) mg/kgBW/day, combination of EEBL-captopril (60+2.5)mg/kgBW/day and combination EEBL-captopril (120+2.5) mg/kgBW/day.  Suspension test were given for 14 days. Observed data is a decrease in blood pressure after giving of the suspension test. Data analysis was performed with the parametric t-test paired and nonparametric Wilcoxon with 95% level of confidence. The result shows that MSG can be as inducer of hypertension. EEBL (60 and 120) mg/kgBW/day has antihypertensive effect. The increase antihypertensive effect of captopril on systolic blood pressure is showed in the treatment EEBL 120 mg/kgBW/day.   Keywords: Hypertension, Monosodium glutamate, Averrhoa bilimbi L.